Lexical-semantic and word-formation processes in modern Ukrainian architecture terminology (on the example of borrowed innovations «graffiti» and «mural») - Кучеренко, Олена Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The purpose of the study is to analyze the features of the use in modern Ukrainian terminological vocabulary of borrowed terminological unit «graffiti» and «mural» and their derivatives for normative use in scientific communication, of logical system presentation of terms- innovations in terminological dictionaries, general dictionary editions. Object of research is Ukrainian terminological vocabulary of architecture in scientific and lexicographic editions. Subject of research is the lexico-semantic and word-formation differences of the innovative adopted nominations «graffiti» and «mural». The research material was scientific texts on architecture, published in printed and electronic special editions, dictionary entries of industry terminological and explanatory dictionaries, dictionaries of synonyms and foreign words. Used descriptive, comparative and structural methods. Attention is paid to the lexical-semantic and word-formation features of innovative architectural borrowed nominations «graffiti» and «mural». As a result of the study, it was determined that the semantic changes and the word-building potential of the analyzed terms confirms the dynamics of modern architectural vocabulary and shows the main trends in its development. In connection with the expansion of the conceptual field, the semantics 0f these innovative borrowed terms have changed significantly, which is not fixed in industry and general terminological dictionaries. At the same time, they became the basis for the formation of new terminological tokens using Ukrainian word-formation tools, as well as analytical terms, while a significant part of the terminological units that are actively used by specialists is not codified. Taking into account the lexical and semantic, derivational differences of these lexemes will contribute to the consistent streamlining, systematization and unification of the architectural terminological fund in lexicographic and special editions.